Pattern of Perioperative Antibiotic Use in Otorhinolaryngology-Head and Neck Surgery at Third Referral Hospital In Surabaya - Nabilah Puspa Utami; Dyah Fauziah; Muhtarum Yusuf (Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia, 2020)
Introduction: Surgical site infection (SSI) often occurs in operation. SSI frequently only affects the superficial tissues, but some more serious infections can affect the deeper tissues or other parts of the body. The majority of SSIs become apparent within 30 days of an operative procedure, when a prosthetic implant is used, SSI may occur several months after the operation. To minimize surgical site infection occurrence, prophylaxis antibiotic is often used. The aim of the study is to evaluate the use of perioperative antibiotics for otorhinolaryngology surgery in third referral hospital in Surabaya.Methods: This study was a retrospective cross-sectional method through the medical record of patients cases from December 2017 to January 2018. All data about sex, age, diagnosis, wound classification, surgical intervention including ICD 9 CM codes, and antibiotics regiments are presented descriptively.Results: Of total 68 patients, 42 (61.8%) were male and 46 (61.8%) were aged 18-65 years old. The most common type of operation was clean surgery 52 (76.5%). The most common prophylactic antibiotic was cefazoline 25 (96.6%). Conclusion: Most of the performed surgery was clean surgery. The use of perioperative antibiotics in most performed operations was in accordance with existing literature. The most widely used prophylactic and therapeutic antibiotic was cefazoline and ceftriaxone, respectively. Further research about risk factor of SSI, the use of prophylaxis antibiotic, and bacterial profile with more samples is needed for more accurate results.